Respostas
respondido por:
0
Método da adição:
2x + 5y = 9 (3)
- 3x - 2y = 5 (2)
6x + 15y = 27
- 6x - 4y = 10 (+)
11y = 37
y = 37
11
2x + 5y = 9
2x + 5. 37 = 9
11
2x + 185 = 9
11
mmc: 11
22x + 185 = 99
11 11
22x + 185 = 99
22x = 99 - 185
22x = - 86
x = - 86 (:2) = - 43
22 (:2) 11
x = - 43
11
2x + 5y = 9 (3)
- 3x - 2y = 5 (2)
6x + 15y = 27
- 6x - 4y = 10 (+)
11y = 37
y = 37
11
2x + 5y = 9
2x + 5. 37 = 9
11
2x + 185 = 9
11
mmc: 11
22x + 185 = 99
11 11
22x + 185 = 99
22x = 99 - 185
22x = - 86
x = - 86 (:2) = - 43
22 (:2) 11
x = - 43
11
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás